2012
DOI: 10.2174/156652412798889063
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activities of Tea Epigallocatechin-3-Gallate in Breast Cancer Patients under Radiotherapy

Abstract: The purpose of this study was to test the hypothesis that administration of epigallocatechin-3-gallate (EGCG), a polyphenol present in abundance in widely consumed tea, inhibits cell proliferation, invasion, and angiogenesis in breast cancer patients. EGCG in 400 mg capsules was orally administered three times daily to breast cancer patients undergoing treatment with radiotherapy. Parameters related to cell proliferation, invasion, and angiogenesis were analyzed while blood samples were collected at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 54 publications
4
87
1
1
Order By: Relevance
“…Activation of p-Akt and the NF-jB/Bcl-2 pathway leads to inhibition of chemotherapy-induced apoptosis, which results in treatment resistance (Wang et al 1996). Our previous results confirmed that suppression of Akt and the NF-jB/Bcl-2 pathway by anticancer agents inhibited the growth and migration as well as induced apoptosis and cell cycle arrest in human lung cancer A549 cells and breast cancer MDA-MB-231 cells Wang et al 2009;Yu et al 2009;Jiang et al 2010;Zhang et al 2012a). In the present study, we indicated that TBrC significantly enhanced the inhibition of the proliferation and migration of LLC cells and the PI3K/Akt and NF-jB pathway by suppressing the phosphorylation and expression of Akt and the NF-jB expression and activating the apoptotic pathway related to changes of Bcl-2/Bax ratio, mitochondrial cytochrome C and caspase-3 in LLC cells.…”
Section: Tbrc Enhances the Migration Inhibition In Llc Cellssupporting
confidence: 72%
See 2 more Smart Citations
“…Activation of p-Akt and the NF-jB/Bcl-2 pathway leads to inhibition of chemotherapy-induced apoptosis, which results in treatment resistance (Wang et al 1996). Our previous results confirmed that suppression of Akt and the NF-jB/Bcl-2 pathway by anticancer agents inhibited the growth and migration as well as induced apoptosis and cell cycle arrest in human lung cancer A549 cells and breast cancer MDA-MB-231 cells Wang et al 2009;Yu et al 2009;Jiang et al 2010;Zhang et al 2012a). In the present study, we indicated that TBrC significantly enhanced the inhibition of the proliferation and migration of LLC cells and the PI3K/Akt and NF-jB pathway by suppressing the phosphorylation and expression of Akt and the NF-jB expression and activating the apoptotic pathway related to changes of Bcl-2/Bax ratio, mitochondrial cytochrome C and caspase-3 in LLC cells.…”
Section: Tbrc Enhances the Migration Inhibition In Llc Cellssupporting
confidence: 72%
“…These were done according to our published methods (Wang et al 2009;Yu et al 2009;Zhang et al 2000Zhang et al , 2012a. In brief, LLC cells were treated for 48 h with TBrC ( .…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry for cell cycle analysis and apoptosis These were done according to our published methods (Wang et al 2009;Yu et al 2009;Zhang et al 2000Zhang et al , 2012a. In brief, LLC cells were treated for 48 h with sodium valproate (VPA, 0.5 mM), coumarin-3-carboxylic acid (HCCA, 0.064 mM), or in combination of VPA (0.5 mM) and HCCA (0.064 mM).…”
Section: Cell Culture and In Vitro Proliferation Assaymentioning
confidence: 99%
“…This was performed according to our published methods with some modifications (Wang et al 2009;Yu et al 2009;Zhang et al 2009Zhang et al , 2012aJiang et al 2010). In brief, LLC cells were treated with different concentrations of sodium valproate (VPA, 0.5-1 mM), coumarin-3-carboxylic acid (HCCA, 0.064-0.125 mM), or in combination of VPA and HCCA, or Ly294002 (Ly, 0.0125 mM), Bay (0.0025 mM).…”
Section: Western Blot Analysismentioning
confidence: 99%